Silver nanoparticle-embedded polymersome nanocarriers for the treatment of antibiotic-resistant infections. Issue 8 (28th February 2015) - Geilich, Benjamin M.; van de Ven, Anne L.; Singleton, Gloria L.; Sepúlveda, Liuda J.; Sridhar, Srinivas; Webster, Thomas J.
<x xml:space="preserve">Abstract</x> The combination of hydrophobic silver nanoparticles and hydrophilic ampicillin inside polymersomes inhibits the growth of drug resistant Escherichia coli in a synergistic, dose-dependent manner.